Efforts To Improve Learning Outcomes Of 100-Meter Running Through Problem-Based Learning Strategies In B-T-S Running Games in Junior High School Students - Maulana Maulana; Epi Supriani Siregar; Arief Rahman (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This research aimed to investigate the effectiveness of Problem-Based Learning (PBL) strategies integrated with Block-Turn-Sprint (B-T-S) running games in improving 100-meter running performance and learning outcomes among junior high school students. Methods: A quasi-experimental design was employed with 60 junior high school students (aged 13-15 years) from Medan City, Indonesia, randomly assigned to experimental (n=30) and control (n=30) groups. The experimental group received PBL-integrated B-T-S running games intervention for 8 weeks, while the control group followed conventional teaching methods. Pre- and post-intervention measurements included 100-meter sprint times, technical skill assessments, and cognitive understanding evaluations. Results: The experimental group demonstrated significantly greater improvements in 100-meter sprint performance (mean improvement: 1.47±0.32 seconds, p<0.001), technical skills (effect size: d=1.23), and cognitive understanding scores (mean difference: 12.8±2.1 points, p<0.001) compared to the control group. Student engagement and motivation levels also increased substantially in the experimental group. Conclusion: Problem-Based Learning strategies combined with B-T-S running games effectively enhance 100-meter running learning outcomes in junior high school students, providing a superior alternative to traditional teaching methods in physical education.